Methylation of cysteinyl leukotriene receptor 1 genes associates with lung function in asthmatics exposed to traffic-related air pollution. Issue 2 (1st February 2021) - Rabinovitch, Nathan; Jones, Meaghan J.; Gladish, Nicole; Faino, Anna V.; Strand, Matthew; Morin, Alexander M.; MacIsaac, Julie; Lin, David T. S.; Reynolds, Paul R.; Singh, Amrit; Gelfand, Erwin W.; Kobor, Michael S.; et al.
ABSTRACT: Air pollution is associated with early declines in lung function and increased levels of asthma-related cysteinyl leukotrienes (CysLT) but a biological pathway linking this rapid response has not been delineated. In this randomized controlled diesel exhaust (DE) challenge study of 16 adult asthmatics, increased exposure-attributable urinary leukotriene E4 (uLTE4, a biomarker of cysteinyl leukotriene production) was correlated (p = 0.04) with declines in forced expiratory volume in 1-second (FEV1 ) within 6 hours of exposure. Exposure-attributable uLTE4 increases were correlated (p = 0.02) with increased CysLT receptor 1 (CysLTR1) methylation in peripheral blood mononuclear cells which, in turn, was marginally correlated (p = 0.06) with decreased CysLTR1 expression. Decreased CysLTR1 expression was, in turn, correlated (p = 0.0007) with FEV1 declines. During the same time period, increased methylation of GPR17 (a negative regulator of CysLTR1) was observed after DE exposure (p = 0.02); this methylation increase was correlated (p = 0.001) with decreased CysLTR1 methylation which, in turn, was marginally correlated (p = 0.06) with increased CysLTR1 expression; increased CysLTR1 expression was correlated (p = 0.0007) with FEV1 increases. Collectively, these data delineate a potential mechanistic pathway linking increased DE exposure-attributable CysLT levels to lung function declines through changes in CysLTR1-related methylation and gene expression.